El «Coronato» napolitano. Una moneda documental y propagandística - Francisco Olmos, José María de (Revista General de Información y Documentación, 2003)
A documental study of the special mintings of the House of Trastamara in the kingdom of Naples (1458-1495) as an example of the use of coin as a document for propaganda and for legitimising the rights of the king to the throne.